NEW CONSTITUTION - THE COUNCIL OF DEVELOPMENT - Sirojiddinov, Asliddin Abduvahidjan ugli (Educational Research in Universal Sciences, 2024)
This article analyzes the role of our newly adopted Constitution in society and human life, the guaranteed rights and freedoms of citizens, the approaches of the newly introduced changes to the practice of law enforcement, and the norms aimed at protecting human rights and interests.